2018
DOI: 10.1016/j.icarus.2018.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry, mixing and transport in Jupiter’s stratosphere constrained by Cassini

Abstract: In this work, we aim at constraining the diffusive and advective transport processes in Jupiter's stratosphere, using Cassini/CIRS observations published by Nixon et al. (2007Nixon et al. ( , 2010. The Cassini-Huygens flyby of Jupiter on December 2000 provided the highest spatially resolved IR observations of Jupiter so far, with the CIRS instrument. The IR spectrum contains the fingerprints of several atmospheric constituents and allows probing the tropospheric and stratospheric composition. In particular, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 88 publications
(200 reference statements)
2
59
0
Order By: Relevance
“…We find that K yy "2ˆ10 8 cm 2¨s´1 , and this value is nominally lower by a factor of 10 than early modeling results from Friedson & Moses (2011). A more accurate derivation of the input fluxes as a function of latitude at Saturn that are responsible for the observations will require additional simulation work with 2D photochemical models (Hue et al 2015(Hue et al , 2016(Hue et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We find that K yy "2ˆ10 8 cm 2¨s´1 , and this value is nominally lower by a factor of 10 than early modeling results from Friedson & Moses (2011). A more accurate derivation of the input fluxes as a function of latitude at Saturn that are responsible for the observations will require additional simulation work with 2D photochemical models (Hue et al 2015(Hue et al , 2016(Hue et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…This improves the predicted temperatures in the middle stratosphere (1 − 10 mbar) by about 2 K. The vertical profiles of hydrocarbons' abundances are held constant with latitude and season, and set as is described in Guerlet et al (2014) using a combination of Cassini observations (Guerlet et al, 2009) and photochemical modeling (Moses et al, 2000). Variations up to 100% of acetylene abundance are observed at high latitudes , note that Sylvestre et al (2015 found weaker variations) which would entail temperature variations of a couple K in the vicinity of the 1-mbar level (Guerlet et al, 2014, section 4.4); coupling our radiative model with a seasonal photochemical scheme is considered as a future development for dedicated middle-to-upper stratosphere GCM simulations (see Challenge C 3 , as well as Hue et al, 2016Hue et al, , 2018. Guerlet et al (2014) showed that this seasonal model allowed for both efficiency and accuracy, with satisfactory comparisons with Cassini measurements -including the observed temperature "knee" caused by heating at the top of the tropospheric aerosol layer, and the meridional gradient between the summer and winter stratosphere (Fletcher et al, 2010a.…”
Section: Building the Modelmentioning
confidence: 94%
“…Kunde et al (2004) and Nixon et al (2007) found that, unlike C 2 H 2 , the zonal mean of C 2 H 6 did not follow the mean insolation and peaked at polar latitudes. Hue et al (2018) demonstrated that this discrepancy between two species that share a similar neutral chemistry cannot be explained either by neutral chemistry or by a combination of advective and diffusive transport. In turn, they proposed ion-neutral chemistry in the auroral region as a mechanism for bringing the zonal mean of C 2 H 6 out of equilibrium with the solar insolation.…”
Section: Discussionmentioning
confidence: 99%
“…4. Details on this profile can be found in Hue et al (2018). We chose to use this disk-averaged temperature profile throughout the 18-yr observation period of Odin because Jupiter barely shows disk-averaged seasonal variability (Hue et al 2018).…”
Section: Temperature and Vertical Transportmentioning
confidence: 99%
See 1 more Smart Citation